The Importance of This and That: Reflections on Context in Early Islamic Philosophy - Phil Enns (Al-Jami'ah Research Centre, 2011)
The discussion over the relationship between what is true globally and what is true locally is not new. It might be helpful, therefore, to consider issues surrounding the relationship between globalization and local values in light of previous forms of this discussion. To this end, I would like to reflect on the discussion of context in the writings of al-Farabi, Ibn Sina and al-Ghazali. To focus this paper, I will consider only three issues, namely that of history, science and the role of reason in religion. I will argue that al-Farabi and Ibn Sina present an account of context that begins with experience as a foundation and then moves to the universal, emphasizing the importance of tradition, demonstration and rationality. Against these two, al-Ghazali argues for the importance of leaving behind experience in order to reach that which is certain, emphasizing the supernatural, intuition and mystical. My goal is to draw out some implications these writers recognized followed from their often dense and esoteric discussions of the nature of particulars and universals, and conclude with some suggestions for our contemporary situation.